AUTO-IMAGE IN THE WRITINGS OF DOMINIK TATARKA - Bátorová, Mária (Porównania, 2018)
Based on previous analyses, this study uses the theoretical discourse of comparative imagology to show the productive aspects of this discipline on the material which can document the relationship between politics and literature. The particular works that were chosen for analysis constitute crucial events in the development of Slovac literature and allow to make references to Central European literature of the 1940s. The paper also focuses on other symptoms: two phases of dissent, internal emigration, internal freedom, some types of self-images and their fulfilment or impact in the structure of literary work. This study informs about the specific type of Slovak literature and aims at providing a de-ideologized picture of Slovak literature as a literature of the rural type.